ChemInform Abstract: High‐Capacity Micrometer‐Sized Li2S Particles as Cathode Materials for Advanced Rechargeable Lithium‐Ion Batteries. Issue 2 (9th January 2013) - Yang, Yuan; Zheng, Guangyuan; Misra, Sumohan; Nelson, Johanna; Toney, Michael F.; Cui, Yi
Abstract The electrochemical study of Li2S as cathode material shows that a large potential barrier (1 V) exists at the beginning of the charge process.